P012 Peptidyl arginine deiminase immunisationinduces anti-citrullinated protein antibodies in HLA-DRB1*04:01 transgenic mice. (21st February 2018) - Auger, I; Arnoux, F; Mariot, C; Peen, E; Lambert, NC; Balandraud, N; Roudier, J
Abstract : Introduction: Autoantibodies to citrullinated proteins (ACPAs) are highly associated with rheumatoid arthritis (RA). ACPAs are produced in the absence of T cell responses to citrullinated proteins. Objectives: Peptidyl arginine deiminase 4 (PAD4), which binds numerous different proteins and citrullinates them, is the target of autoantibodies in early RA. This suggests a model to explain the production of ACPAs in the absence of T cells to citrullinated proteins. ACPAs could arise because, at first, PADs are recognised by T cells, which, in turn help the production of autoantibodies to proteins being citrullinated by PADs, through a hapten/carrier model. Here, we test this model in mice. Methods: HLA-DRB1*04:01 transgenic mice were immunised subcutaneously with PADs or phosphate buffered saline (PBS) in Freund's complete adjuvant (CFA). Three booster injections of PAD or PBS in Freund' incomplete adjuvant (IFA) were given subcutaneously 15, 35 and 55 days later. Mice were: tested for anti-PAD antibodies by ELISA. tested for T cell responses to PADs, native or citrullinated fibrinogen 65 days after PAD immunisation. tested for anti-citrullinated fibrinogen antibodies by ELISA using fibrinogen peptides under citrullinated and native form. Results: HLA-DRB1*04:01 transgenic mice immunised with PADs developed antibodies and T cells to PADs and IgG antibodies to citrullinated peptides from fibrinogen, in the absence of T cell response to native or citrullinated fibrinogen. Conclusions: T cell immunisation to PAD proteins triggers ACPAs through a hapten carrier mechanism in which the carrier is PAD which performs citrullination and the hapten any protein being citrullinated by PAD. Disclosure of interest: None declared